Conversion Disorder and Visual Disturbances in Children. - Bonci, Fabrizio (Journal of Behavioral Optometry, 2012)
Conversion disorder is a neurological disturbance in which systemic symptoms are unconscious, thus not under the control of the child. Conversion disorder is a manifestation of a stressful or traumatic event. Physical symptoms may occur with motor and sensorial disturbances, including visual reactions which may lead the practitioner to suspect an organic cause. Visual symptoms include visual acuity reduction in one or both eyes, visual field defects, intermittent diplopia, and disturbances with reading and writing. Diagnosis of the conversion disorder may be difficult at the initial presentation because physical complaints are considered the primary issues that require resolution. The diagnosis is commonly made after consultation among a variety of practitioners such as the pediatrician, optometrist, neuro-ophthalmologist, and pediatric neurologist. Therefore, it is important for optometrists, especially for those who work in pediatric settings, to understand conver-sion disorder and the possible visual and systemic manifestations.